2020
DOI: 10.1186/s12966-020-00953-4
|View full text |Cite
|
Sign up to set email alerts
|

Like me, like you – relative importance of peers and siblings on children’s fast food consumption and screen time but not sports club participation depends on age

Abstract: Background: Lifestyle interventions to prevent paediatric obesity often target family and peer settings; their success is likely to depend on the influence that peers and families exert on children's lifestyle behaviors at different developmental stages. Objective: First, to determine whether children's lifestyle behavior more closely resembles their peers' or siblings' behaviors. Secondly, to investigate longitudinally whether children's behavioral change is predicted by that of their peers or their siblings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Furthermore, fast food consumption and screen time behaviour were more similar between younger siblings, while these behaviours were more similar with the behaviour of peers than siblings in older children. 42 In summary, our findings show that parental structure and sibling status are independently associated with children's BMI. Hence, public health actions should focus particularly on supporting non-traditional families and only children in maintaining a healthy weight.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, fast food consumption and screen time behaviour were more similar between younger siblings, while these behaviours were more similar with the behaviour of peers than siblings in older children. 42 In summary, our findings show that parental structure and sibling status are independently associated with children's BMI. Hence, public health actions should focus particularly on supporting non-traditional families and only children in maintaining a healthy weight.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, Bogl et al 42 observed that near‐aged siblings' behaviour is more similar than the behaviour of siblings with a larger age gap. Furthermore, fast food consumption and screen time behaviour were more similar between younger siblings, while these behaviours were more similar with the behaviour of peers than siblings in older children 42 …”
Section: Discussionmentioning
confidence: 99%
“…Schools in many countries have been closed for several months. Under this situation, no access to school lunch and lack of supervision from teachers and parents (who are often working) for their food choices and dietary habits is another factor to consider [ 35 ]. On the other hand, in some countries such as Finland, school kitchens provide take-away food for pupils during distance-learning.…”
Section: Impact Of Covid-19 and Related Quarantine Procedures On Metabolic Riskmentioning
confidence: 99%
“…The influential study by Christakis and Fowler [1] was among the first to demonstrate the importance of friendship relations for weight status and risk of developing overweight and obesity in adults [1, 2]. Friends’ similarities in body weight are already observed in adolescence, a formative period with increasing peer and decreasing familial influence, and include similarities in predictors of body weight such as diet, exercise, sedentary behavior, and weight concerns [3-8]. It is not clear whether the observed similarities reflect peer influence or homophily, the latter describing the selection of friends because of existing behavioral or social similarities [6, 9].…”
Section: Introductionmentioning
confidence: 99%